COMPUTER LABORATORY MANAGEMENT IN IMPROVING THE QUALITY OF STUDENT LEARNING AT SMA AL-MINHAJ SHAHABAH TAMANSARI BOGOR - M Hidayat Ginanjar; Muhamad Syukur; Rahman Rahman (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2023)
This research aimed to investigate the procurement, use, and maintenance of the computer laboratory equipment at SMA Al-Minhaj Shahabah. This study used a qualitative case study approach because it described the use of the computer laboratory in supporting the teaching and learning process at SMA Al-Minhaj Shahabah. The data were collected through observation, interviews, and document study. The data analysis techniques used were data reduction, presentation, and verification. The data validity techniques used credibility, transferability, dependability, and confirmability. The results showed, among others: (1) Laboratory use and maintenance system was quite good. The maintenance of computer laboratory equipment has been planned in the School Development Plan (RPS) in general regarding the planning, process, and results obtained from the maintenance, (2) The design and layout of the laboratory were quite effective. (3) There was a schedule for effective laboratory use, (4) There were still obstacles for teachers and students in teaching and learning in the laboratory. (5) Laboratory management was handled by educational expert staff, and there was support from the foundation